Safety belt and mobile phone usage in vehicles in Barcelona (Spain) - Jose M Martínez-Sánchez; Ariadna Curto; Marcela Fu; Cristina Martínez; Xisca Sureda; Montse Ballbè; Esteve Fernández (Elsevier, 2014)
Objectives: To describe the prevalence and correlates of safety belt and mobile phone usage in vehicles in the city of Barcelona (Spain). Methods: We performed a study using direct observation with a cross-sectional design. We selected 2,442 private cars, commercial vehicles, and taxis from all districts of Barcelona. Results: The prevalence of people not wearing safety belt was 10.5% among drivers, 4.6% among front seat passengers, and 32.2% among some of the rear passengers. It was higher among the passengers than among the drivers, regardless of the type of the vehicle. The prevalence of mobile phone usage while driving during a moment of the trip was 3.8%. Conclusion: Our study shows noticeably high prevalence of people not wearing safety belt in the rear seats. Moreover, four out of one hundred drivers still use the mobile phone while driving during a moment of the trip.